FORMULASI SEDIAAN BALSEM DARI EKSTRAK DAUN KEMANGI (Ocimum SanctumLinn) DAN PEMANFAATANNYA SEBAGAI OBAT TRADISIONAL - Wahyuddin Jumardin; Safaruddin Amin; Nurhidayati M. Syahdan (As-Syifaa Jurnal Farmasi, 2015)
The research has conducted to produce balm basil leaf extract which aims to discover how to formulating preparations balm from basil leaf extract (Ocimum sanctum Linn) as a tradisional medicine. The results of research that basil leaf extract can be made in the preparation as a balm. This is indicated through organoleoptic observation and the homogeneity of the preparation is stable.